Social Problems of Psychiatric Patients: A Field Study and a Social Vision in The Psychiatric Hospital in Erbil - Sedeeq Mohammad Hamasharif; Zarya Ahmad Taher (QALAAI ZANIST JOURNAL, 2022)
This thesis attempts to study the social problems of psychiatric patients, which were diagnosed through a field study and a social vision in the Psychiatric Hospital in Erbil. Therefore, such studies are worthy of research, because they bring into existence the social problems that psychiatric patients suffer from, such as depression, isolation or social isolation, difficulty in social adjustment, emotional deprivation and other problems that prevent them from performing the social and functional roles entrusted to them, and not to make decisions related to his future, his family and his surroundings. In order to achieve the objectives of the research, data and information collection was resorted to using two approaches: the case study of psychiatric patients, each on the individual, and the social survey by means of a questionnaire. (53) forms were distributed For analysis of application research, we are using statistical instrument such as, The Arithmetic Mean, Weighted Mean Standard Deviation, Correlation superman, (T-TEAST) for one sample and for this purpose by reference to the (Statistical Package for Social Science) SPSS The study reached a number of important conclusions, that the attention and family care provided by the family to the mentally ill are almost weak due to the weakness and low social awareness of the families. and his health. And it is these beliefs that drive mental illness to resort to unscientific methods in the treatment or treatment of mental illness.